The Global Landscape of Corporate Criminal Responsibility: Between a Culture of Compliance and Law Enforcement: The Global Landscape of Corporate Criminal Responsibility: Between a Culture of Compliance and Law Enforcement - Badrut Tamam; Maryano Maryano; Alan Robert White (PENA LAW: International Journal of Law, 2026)
Corporate criminal liability has become a strategic issue in the era of globalization, when multinational corporations play a role as economic drivers while also having the potential to commit transnational crimes. Differences in legal approaches between countries, particularly between common law and civil law systems, create disparities in the scope, enforcement, and philosophy of liability. This study aims to conduct a comparative analysis of the legal framework for corporate criminal liability in the United States, the United Kingdom, Germany, Japan, and Indonesia, with a focus on the relationship between law enforcement mechanisms and compliance culture. The method used is normative-comparative legal research with analysis of regulations, court decisions, policy documents, and international guidelines such as those of the OECD and UNODC. The results show that the common law system adopts the vicarious liability model and hybrid mechanisms such as Deferred Prosecution Agreements (DPAs), while civil law relies more on administrative sanctions. Indonesia is in a transitional phase with explicit recognition but inconsistent implementation. This study recommends an integrative model that combines deterrence-based law enforcement with institutional reform as an effort toward global harmonization of corporate accountability.